Pengaruh Analisis Jabatan dan Pengembangan Karir terhadap Kinerja Pegawai Kantor Kecamatan Cilacap Tengah Kabupaten Cilacap - Heni Ajeng Wijayanti; Apri Budianto; Ferey Herman (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
Employees of the Cilacap Tengah District Office, Cilacap Regency often receive criticism from the public. The District itself certainly considers the criticism to be an encouragement and motivation to make the institution's performance even better. This performance improvement can be done through job analysis and career development of each member of the Cilacap Tengah District Office Employees. This study aims to determine 1). Analysis of the influence of positions on the performance of Cilacap Tengah District Office Employees, 2). The influence of career development on the performance of Cilacap Tengah District Office Employees, and 3). Analysis of the influence of positions and career development on the performance of Cilacap Tengah District Office Employees. Therefore, this study uses quantitative research which then interprets the data to produce descriptive data. While the data collection technique uses a questionnaire, and data analysis uses multiple linear regression. The results of the study indicate that job analysis and career development have a positive effect on the performance of Cilacap Tengah District Office Employees. If job analysis and career development are better, then the performance of the members will also be better, and vice versa if job analysis and career development are worse, then the performance of the Cilacap Tengah District Office Employees will also decrease.